OH production from the photolysis of isoprene-derived peroxy radicals: cross-sections, quantum yields and atmospheric implications. Issue 3 (5th January 2017) - Hansen, Robert F.; Lewis, Tom R.; Graham, Lee; Whalley, Lisa K.; Seakins, Paul W.; Heard, Dwayne E.; Blitz, Mark A.
Abstract : The OH radical production from the near-ultraviolet photolysis of peroxy radicals derived from isoprene has been investigated. Abstract : In environments with high concentrations of biogenic volatile organic compounds and low concentrations of nitrogen oxides (NO x = NO + NO2 ), significant discrepancies have been found between measured and modeled concentrations of hydroxyl radical (OH). The photolysis of peroxy radicals from isoprene (HO-Iso-O2 ) in the near ultraviolet represents a potential source of OH in these environments, yet has not been considered in atmospheric models. This paper presents measurements of the absorption cross-sections for OH formation ( σ RO2, OH ) from the photolysis of HO-Iso-O2 at wavelengths from 310–362.5 nm, via direct observation by laser-induced fluorescence of the additional OH produced following laser photolysis of HO-Iso-O2 . Values of σ RO2, OH for HO-Iso-O2 ranged from (6.0 ± 1.6) × 10 −20 cm 2 molecule −1 at 310 nm to (0.50 ± 0.15) × 10 −20 cm 2 molecule −1 at 362.5 nm. OH photodissociation yields from HO-Iso-O2 photolysis, ϕ OH, RO2, were determined via comparison of the measured values of σ RO2, OH to the total absorption cross-sections for HO-Iso-O2 ( σ RO2 ), which were obtained using a newly-constructed spectrometer. ϕ OH, RO2 was determined to be 0.13 ± 0.04 at wavelengths from 310–362.5 nm. To determine the impact of HO-Iso-O2 photolysis on atmospheric OH concentrations, a modeling case-study for a high-isoprene, low-NO x environment (namely, the 2008 Oxidant and Particle Photochemical Processes above a South-East Asian Tropical Rainforest (OP-3) field campaign, conducted in Borneo) was undertaken using the detailed Master Chemical Mechanism. The model calculated that the inclusion of HO-Iso-O2 photolysis in the model had increased the OH concentration by only 1% on average from 10:00–16:00 local time. Thus, HO-Iso-O2 photolysis alone is insufficient to resolve the discrepancy seen between measured OH concentrations and those predicted by atmospheric chemistry models in such environments.